A Study on Environmental Sustainability Practices among Students and Staff in International Islamic University Malaysia (IIUM) - Ninunroihan Jehtae; Arita Hanim Awang; Noraini Ahmad (International Journal of Emerging Issues in Islamic Studies, 2021)
This study is conducted to assess awareness and engagement on campus environmental sustainability initiatives among the students and staff of International Islamic University Malaysia (IIUM). In this research, a quantitative method was employed and a total of 100 survey questionnaires were randomly distributed to respondents. Based on the survey, 90.7% of the respondents are aware of the term "sustainability” and are mostly concerned on the energy and water consumption in campus. However, there seems to be a deliberate commitment gap due to given answers by respondents in having insufficient time to engage in environmental sustainability. On the other hand, it is found that IIUM has made some positive impacts with initiatives such as promoting waste recycling practices, efficient use of energy, water and many more in considering ways and means to deal more efficiently with environmental issues. The findings suggested that the university could address sustainability issues through other initiatives as in transportation, sustainable landscaping, and sustainable food. The article concluded by emphasizing the importance of integrating sustainability on campus as well as on the respective curriculum and educating university students to assist in sustainable development across Malaysia.